Qualitative identification of factors related to bereavement in covid-19 mourners - Farnoosh Khaledi Alamdari; Roya Koochakentezar; Fatemeh Golshani; Abbas Zabihzadeh (مجله علوم روانشناختی)
Background: The covid-19 disease has caused death shock all over the world. The consequences of the Covid-19 pandemic can lead to complex and long-term bereavement in a large number of people. In previous studies, the lived experience of bereavement in the context of the family has been less studied; especially regarding the identification of factors related to bereavement in the bereavement in covid-19 mourners, there is a research gap. Aims: The present study was conducted with the aim of identifying the factors related to bereavement in the mourners of Covid-19. Methods: This study was conducted with a qualitative approach and using the phenomenological method. The statistical population of the research included all women living in Tehran who had lost one of their first-degree relatives (including sisters, brothers, parents or spouses) due to the disease of Covid-19. During this study, using purposeful sampling, 25 women were subjected to semi-structured in-depth interviews from May 2021 to October 2022. The conducted interviews were also analyzed in six stages using the thematic analysis method of Brown and Clark (2006). Results: The data analysis of this research led to the identification of 236 primary codes, 22 secondary themes, 22 main themes and 6 Canopy themes (Incomplete bereavement, coping strategies, multifaceted grief, attachment style, identity change and the meaning of death). Conclusion: The results obtained from the present study showed that the factors related to bereavement in covid-19 mourners are different from normal bereavements, Therefore, it is suggested that psychologists specializing in bereavement use the themes identified in the present study to develop treatment protocols related to the treatment of bereavement in women